Needlestick Injuries among Nurses in a Tertiary Care Hospital: A Work Hazard or Lack of Awareness? - Angrup, Archana; Kamlesh, Thakur; Chand, Jaryal Subhash; Anuradha, Sood; Lata, Chandel (Asian Journal of Medical Sciences, 2013)
Objectives: The present study addresses this important issue of NSI and aims at determining their occurrence among the nursing staff in Dr Rajendra Prasad Government Medical College (RPGMC) and hospital, Kangra at Tanda (H.P). Methods: A cross sectional study undertaken amongst the nursing staff of Dr RPGMC and hospital, Kangra at Tanda. Results: Out of the 164 respondents, 35(21.3%) reported to having one or more NSIs in their career and the maximum of these were amongst the nurses whose work experience was less than five years (13.4%). Conclusions: The results of this study confirm the importance of the need for an increased awareness of the risk of needlestick injury, the need to provide for the training and education of health-care workers DOI: http://dx.doi.org/10.3126/ajms.v5i1.4971 Asian Journal of Medical Science Vol.5(1) 2014 pp.58-62